2012
DOI: 10.4049/jimmunol.1201207
|View full text |Cite
|
Sign up to set email alerts
|

A2B Adenosine Receptor Expression by Myeloid Cells Is Proinflammatory in Murine Allergic-Airway Inflammation

Abstract: Asthma is a chronic condition with high morbidity and healthcare costs, and cockroach allergens are an established cause of urban pediatric asthma. A better understanding of cell types involved in promoting lung inflammation could provide new targets for the treatment of chronic pulmonary disease. Due to its role in regulating myeloid cell dependent inflammatory processes, we examined A2B R expression by myeloid cells in a cockroach allergen (CRA) model of murine asthma-like pulmonary inflammation. Both system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…In general, activation of A2ARs has anti-inflammatory effects (15; 16; 35; 36), whereas activation of A2BRs promoted inflammatory responses (11; 18; 37). However, this does not apply to all immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, activation of A2ARs has anti-inflammatory effects (15; 16; 35; 36), whereas activation of A2BRs promoted inflammatory responses (11; 18; 37). However, this does not apply to all immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not apply to all immune responses. For example, proinflammatory effects have been seen as a result of A2AR activation (11; 18) and anti-inflammatory effects of A2BR activation have been reported (11; 3840). A study in A2AR −/− mice showed that they developed more severe EAE than syngeneic B6 mice, but treatment of wild-type B6 mice with an A2AR antagonist inhibited, rather than enhanced, the development of EAE (21), suggesting that the mechanisms by which adenosine agonists/antagonists affect an immune response is more sophisticated than currently thought.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that smooth muscle cells can signal through the A2bR to induce the downregulation of IFNγ-induced major histocompatibility class II expression (27). A2bR signaling appears to promote anti-inflammatory macrophages, however other studies have associated A2bR with inflammatory roles in disease models such as asthma, thus demonstrating diverse and perhaps tissue-specific roles for A2bR in the regulation of inflammation (28). …”
Section: Discussionmentioning
confidence: 99%
“…The important role of adenosine and adenosine receptors in activation of monocytes and monocyte-derived mature myeloid cells (macrophages and inflammatory DCs) has been demonstrated in many studies using animal models of lung inflammation [15,16,30,31]. Growing evidence indicates that levels of adenosine receptors expression are changed in the lungs of patients with BA and chronic obstructive pulmonary disease [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated a pro-inflammatory role of A 2B during chronic pulmonary inflammation using a mouse model of allergen-induced chronic pulmonary inflammation [15]. The role of A 2B signaling in pro-inflammatory activation of monocytes has been further demonstrated in an allergic-airway inflammation with myeloid cell specific deletion of Adora2b in mouse models [16]. However, little is known about the expression of ADORA in monocytes and their functional properties in patients with BA.…”
Section: Introductionmentioning
confidence: 99%